Parasitism Potential and Laboratory Rearing of Psyllaephagus sp., a Newly Discovered Parasitoid of Cacopsylla chinensis - Zifang Qin; Mingyue Feng; Liu Zhang; Yang Ge; Xinzheng Huang; Wangpeng Shi (Agronomy, 2023)
Psyllaephagus sp. (Hymenoptera: Encyrtidae) is a newly recognized and important parasitoid of Cacopsylla chinensis (Yang and Li) (Hemiptera: Psyllidae), a pest of pear orchards. Its parasitism potential and rearing were studied in the laboratory. The studies showed that the most suitable hosts were fourth- and fifth-instar nymphs of pear psyllids (C. chinensis). The development duration of Psyllaephagus sp. females and males was 15.25 ± 0.37 and 13.57 ± 0.27 days when laying eggs in fourth-instar psyllid nymphs. The wasps did not survive longer than three days when they were fed only water, while they survived about an average of 20 days (23.20 ± 1.12 for females and 19.00 ± 0.80 for males) when fed 20% honey water. The provision of honey water could thus increase adult parasitoid longevity significantly. The lifetime fecundity of Psyllaephagus sp. females was 21.60 ± 0.88. Tests of parasitoid efficiency showed that the wasp’s functional response was Holling type II, with the number of hosts parasitized increasing with the host density to a maximum parasitism rate. The model suggested that a single Psyllaephagus sp. female could parasitize a maximum of 13.66 nymphs per day. The mutual interference of foraging Psyllaephagus sp. females occurred at high parasitoid densities. Psyllaephagus sp. has potential as a biocontrol agent for use against C. chinensis.